Excision of 93 loose bodies of synovial osteochondromatosis in the left ankle: a case report - Dradjat, Respati S.; Pradana, Ananto S.; Salim, Fajar S.; Oktafandi, I. Gusti Ngurah A. A. (International Journal of Research in Medical Sciences, 2020)
Primary synovial osteochondromatosis is an uncommon benign joint disorder characterized by the formation of cartilaginous bodies within the synovial of the different joints, tendon sheaths, and bursae. Loose bodies occur in the late stage of the disease. Excision of loose bodies is needed to treat synovial osteochondromatosis. A 20-year-old female patient presented to us with a chief complaint of pain, swelling, and discomfort sensation in the left ankle while walking. Plain X-ray on her left ankle showed loose bodies surrounding the ankle. We performed excision to remove the loose bodies. Histological examination confirmed the diagnosis. The range of motion (ROM) of the ankle increased after surgery. The patient was able to walk more comfortably. Synovial osteochondromatosis is considered benign. In this case, open excision was chosen because the ankle joint is not amenable to arthroscopy. Follow up is needed to detect early recurrence and transformation of malignancy.